Exponential synchronization of quaternion-valued switching neural networks with mixed delays - Tan, Wei; Zhao, Yongxiang; Peng, Tao; Tu, Zhengwen; Dong, Yuan (Nonlinear Analysis: Modelling and Control, 2026)
This paper investigates the exponential synchronization problem for a class of quaternion-valued switching neural networks (QVSNNs) with mixed time delays and sampled-data control. By using a Lyapunov function method involving sampling instants, sufficient conditions for the synchronization of the considered neural networks (NNs) are obtained in the form of linear matrix inequalities (LMIs). It is worth emphasizing that this paper reduces the conservativeness of stability criteria by combining the free-weight matrix method with discrete sampling points; moreover, the derived criteria are valid for both quaternion-valued and nonasynchronous switching NNs. Finally, the feasibility of the proposed approach is verified by two numerical examples.
Keywords: quaternion-valued switching neural networks; mixed delay; LMIs; sampled-data control